The reliance on conceptual frameworks in qualitative research – a way forward - Joanna E. M. Sale; Leslie Carlin (BMC Medical Research Methodology)
Abstract Background While acknowledging that theory can be critical to scientific progress, we are concerned about instances of its tendency to encroach on, or replace, deep engagement with data in qualitative research. We discuss conceptual frameworks’ role in conducting and teaching qualitative research. Methods We address three questions about our attachment as researchers to theory through conceptual frameworks: (1) What do conceptual frameworks offer qualitative research?; (2) Why do researchers use and teach conceptual frameworks in qualitative research?; and (3) How can we practice and teach rigour while integrating conceptual frameworks in qualitative research? Results One way that theory may be misused in qualitative research is in the development and reliance on conceptual frameworks as a prescription for data collection and analysis. We suggest possible ways forward to ensure rigour while integrating frameworks in qualitative research, such as examining the evolution of our own theoretical perspectives. Conclusions We need to impart to our students the value of thinking deeply about their own data, of knowing what came before, and of taking the time and making an effort to unite these strands into novel and interesting results.